The Sustainability of Asia's Debt (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a [CC BY 3.0 IGO] License. It is free to read, download and share on Elgaronline.com. Asia has shown the world what success in economic development looks like. From the amazing transformations of Japan, the Republic of Korea, and the other 'tigers' in the early 70s, to the more recent takeoffs of the People's Republic of China (PRC), India, and the leading economies in Southeast Asia, the region has prospered at a startling pace. Technologies were adopted, productivity raised, and export markets conquered. Billions were lifted out of poverty. What was once a backwater is now a global engine of growth.